Kajian Numerik Penerapan Turbin Hydrokinetic Darrieus Sebagai Wave and Current Energy Converter Dengan Variasi Sudut Serang dan Solidity - Muhamad Agus Prasetyo M; Burniadi Moballa; George Endri Kusuma (Proceedings Conference on Marine Engineering and its Application, 2023)
The ocean is the largest source of potential energy in Indonesian country, one potential thatcan be expoloites is energy from sea wave and current which can be alternative to meet national energyneeds, ocean wave and current energy includes EBT resources which is rarely explored. Ocean wave andcurrent energy conversion can be converted into electrical energy by use the movement of sea waterwave, hydrokinetic Darrieus tubine is a conversion tool that can be used to convert kinetic energy intomechanical energy, In this case study, used angle of attack and solidity variation of the hydrokineticDarrieus tubine were used, the wave data used is the Southern Waters of Java Island, which is preciselyat Tanjung Bili Beach, Malang. By ussing airfoil NACA 0018 and profile Darrieus turbine diameter of 1m. Produce RMS CT and CP values with the stable is found on the solidty variation 0,15 with angle ofattack 10o TSR 0,25 omega (?) 0,5 with RMS value of CT 0,1512 and CP 0,075.